Maternal prebiotic supplementation reduces fatty liver development in offspring through altered microbial and metabolomic profiles in rats. Issue 4 (10th January 2019) - Paul, Heather A.; Collins, Kelsey H.; Nicolucci, Alissa C.; Urbanski, Stefan J.; Hart, David A.; Vogel, Hans J.; Reimer, Raylene A.
ABSTRACT: A maternal high‐fat/sucrose diet, in the presence of maternal obesity, can program increased susceptibility to obesity and metabolic disease in offspring. In particular, nonalcoholic fatty liver disease risk is associated with poor maternal nutrition and obesity status, which may manifest via alterations in gut microbiota. Here, we report that in a preclinical model of diet‐induced maternal obesity, maternal supplementation of a high‐fat/sucrose diet with the prebiotic oligofructose improves glucose tolerance, insulin sensitivity, and hepatic steatosis in offspring following a long‐term high‐fat/sucrose dietary challenge compared with offspring of untreated dams. These improvements are associated with alterations in gut microbial composition and serum inflammatory profiles in early life and improvements in inflammatory and fatty‐acid gene expression profiles in tissues. Serum metabolomics analysis highlights potential metabolic links between the gut microbiota and the degree of steatosis, including alterations in 1‐carbon metabolism. Overall, our data suggest that maternal prebiotic intake protects offspring against hepatic steatosis and insulin resistance following 21 wk of high fat/sucrose diet, which is in part due to alterations in gut microbiota.—Paul, H. A., Collins, K. H., Nicolucci, A. C., Urbanski, S. J., Hart, D. A., Vogel, H. J., Reimer, R. A. Maternal prebiotic supplementation reduces fatty liver development in offspring through altered microbial and metabolomic profiles in rats. FASEB J. 33, 5153–5167 (2019). www.fasebj.org